1991
DOI: 10.1159/000284700
|View full text |Cite
|
Sign up to set email alerts
|

Speech Characteristics in Depression

Abstract: This study examined the relationship between speech characteristics and psychopathology throughout the course of affective disturbances. Our sample comprised 20 depressive, hospitalized patients who had been selected according to the following criteria: (1) first admission; (2) long-term patient; (3) early entry into study; (4) late entry into study; (5) low scorer; (6) high scorer, and (7) distinct retarded-depressive symptomatology. Since our principal goal was to model the course of affective disturbances i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…Here, most studies have found a decrease in F0 after therapy or during positive mood states (Askenfelt & Sjoelin, 1980;Kuny & Stassen, 1993;Tolkmitt, Helfrich, Standke, & Scherer, 1982) whereas one study suggested an increase in F0 . No significant effects were found by Nilsonne (1987) and Stassen et al (1991).…”
Section: Fundamental Frequency Of the Voice And Depressionmentioning
confidence: 80%
See 1 more Smart Citation
“…Here, most studies have found a decrease in F0 after therapy or during positive mood states (Askenfelt & Sjoelin, 1980;Kuny & Stassen, 1993;Tolkmitt, Helfrich, Standke, & Scherer, 1982) whereas one study suggested an increase in F0 . No significant effects were found by Nilsonne (1987) and Stassen et al (1991).…”
Section: Fundamental Frequency Of the Voice And Depressionmentioning
confidence: 80%
“…In most studies, depressive speech has been found to have a rather narrow range as well as a restricted variability for F0 (Newman & Mather, 1938;Zuberbier, 1957;Ostwald, 1964;Hargreaves, Starkweather, & Blacker, 1965;Bannister, 1972). Accordingly, F0 range widens and variability increases after successful therapy and mood improvement (Kuny & Stassen, 1993;Nilsonne, 1987;Stassen et al, 1991). However, there are a few cases where the opposite effect, .…”
Section: Fundamental Frequency Of the Voice And Depressionmentioning
confidence: 99%
“…Therefore a speaker with a breathy voice, due to reasons unrelated to depression, could present as a false positive in a classifier based purely on NAQ. Similarly errors could be introduced to a prosodic based classifier due simply due to natural variations in speaking style (Nilsonne et al, 1987;Stassen et al, 1991). However using this same set of effects (Table 2), we can infer that depression produces a wide range of alterations in speech motor control, i.e.…”
Section: Alterations In Speech Motor Controlmentioning
confidence: 95%
“…Darby and Hollien (1977) found listeners of speech recorded from depressed patients could perceive differences in the pitch, loudness, speaking rate, and articulation before and after treatment. Acoustical signal-processing technology available at the time was not adequate to cross-validate the subjective observations, but has been refined for analysis of depression-related speech characteristics over subsequent decades (e.g., Darby, Simmons, & Berger, 1984;Kuny & Stassen, 1993;Nilsonne, 1987Nilsonne, , 1988Scherer & Zei, 1988;Stassen, 1988;Stassen, Bomben, & Gunther, 1991). In recent years, advances in the techniques for eliciting and analyzing speech samples have been reported and validated in the literature (e.g., Alpert, Pouget, & Silva, 2001;Alpert, Shaw, Pouget, & Lim, 2002;Breznitz, 2001;France, Shiavi, Silverman, Silverman, & Wilkes, 2000;Garcia-Toro, Talavera, Saiz-Ruiz, & Gonzalez, 2000;Parsa & Jamieson, 2001;Stassen, Kuny, & Hell, 1998;Wuyts et al, 2000).…”
Section: Biomarkers Of Depression In Voice Acousticsmentioning
confidence: 99%